Evolutionary and biologically inspired music, sound, art and design : 5th International Conference, EvoMUSART 2016, Porto, Portugal, March 30-April 1, 2016, Proceedings /: 5th International Conference, EvoMUSART 2016, Porto, Portugal, March 30-April 1, 2016, Proceedings. (2016) - Unknown
No abstract available